PERAN KUALITAS AUDIT DALAM MEMODERASI PENGARUH PENGUNGKAPAN ESG TERHADAP NILAI PERUSAHAAN - Dea Tiara Monalisa Butar-Butar; Nur Alisha Ainaya; Mariska Ramadana (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
This research seeks to analyze the role of audit quality in strengthening or weakening the impact of ESG disclosure on firm value (a case study of companies included in the ESG list on the Indonesia Stock Exchange (IDX) during the 2020-2022 period). The disclosures of environmental, social, and governance aspects are regarded as independent variables. Audit quality plays the role of a moderating variable. The dependent variable in this study is firm value. Agency theory and signaling theory underpin this research. The secondary data used in this study comes from the IDX, covering the years 2020 to 2022. The sample selection in this study was carried out through a targeted sampling approach, resulting in 102 observations. A moderated regression technique was applied to assess the hypotheses. The findings suggest that transparency in environmental, social, and governance aspects does substantially impact corporate value. Furthermore, audit quality as a moderating factor meaningfully affect the corporate valuation.